Employability skills among the students of technical and vocational training centers in Malaysia - Kazilan, Fitrisehara; Hamzah, Ramlah; Bakar, Ab. Rahim (Eurojournals, 2009)
The purpose of this research is to investigate the level of employability skills among the students of a technical and vocational training institutions. There are about 436 final year students from the institution were chosen as a sample of this research. The data was collected by questionnaires which was adapted from Secretary’s Commission on Achieving Necessary Skills (SCANS). Descriptive analysis and inferences such as ANOVA, and t-test were used to analyzed the data. This finding showed that the majority of the respondents are male. Most of them pursuing education in Certificate of Skills in one of these five area of specializations: art and building, electric, electronics, automotive and mechanical. The finding indicated that the employability skills among students were average. The findings also shown that there was a significant difference between employability skills and area of specializations. There were significant difference between employability skills for basic skills and informational skills and gender. The study suggests that Technical and Vocational Educational Department should provide a curriculum which includes employment element skills which are needed by the employers. The institutions and the industry should also create a compact joint-venture for students need in order to produce higher quality workers.